Characterization of Stone Cleaning by Nd:YAG Lasers with Different Pulse Duration. (19th February 2007) - Bartoli, Laura; Pouli, Paraskevi; Fotakis, Costas; Siano, Salvatore; Salimbeni, Renzo
Abstract : The present work is a comparative study on the laser cleaning of stonework using Nd:YAG lasers at different pulse durations. The ablation rate, the degree of cleaning, and the appearance of the treated surface were studied irradiating a simulated sample and a real stone artefact using three different Nd:YAG laser systems with pulse duration of 90 microseconds, 15 nanoseconds, and 150 picoseconds. To our knowledge, the picosecond laser is here used for the first time in stone conservation. Differences in efficiency and in cleaning result are shown and discussed.